Fast, Accurate, and Practical Identity Inference Using TV Remote Controls - Phielip, Mariano; Galan, Magdiel; Lee, Richard; Kveton, Branislav; Hightower, Jeffrey (Proceedings of the AAAI Conference on Artificial Intelligence, 2010)
Non-invasive identity inference in the home environment is a very challenging problem. A practical solution to the problem could have far reaching implications in many industries, such as home entertainment. In this work, we consider the problem of identity inference using a TV remote control. In particular, we address two challenges that have so far prevented the work of Chang et al. (2009) from being applied in a home entertainment system. First, we show how to learn the patterns of TV remote controls incrementally and online. Second, we generalize our results to partially labeled data. To achieve our goal, we use state-of-the-art methods for max-margin learning and online convex programming. Our solution is efficient, runs in real time, and comes with theoretical guarantees. It performs well in practice and we demonstrate this on 4 datasets of 2 to 4 people.